Use of Gadgets with Screen Time on Emotional Intelligence in The Digital Era in Middle Adolescence (15-18 Years) - Marchamah, Dwi Nur Siti; Sudrajat, Agus; Rahmatika, Dena Nur (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Gadget addiction causes various personality disorders. This study is to determine whether the use of gadgets with screen time has an effect on emotional intelligence. This research uses the cross-sectional method. The research variables are gadgets as an independent variable, screen time as an intervening variable, and emotional intelligence as a determining variable. The population of adolescents is the middle adolescence (15-18 years) SMA X Semarang City as many as 252 people. Using a minimum sample of 100 people, with a cluster random sampling technique. Data analysis using Path Analysis. Validity test with a 5% confidence level of 0.374. The calculated r-value > r-table. The reliability test used Cronbach Alpha with the results of the reliability value > 0.7. Research results: (1) The significance value of 0.751 > 0.05 means that the use of gadgets does not affect screen time. (2) The significance value of 0.025 < 0.05 means that the use of gadgets affects emotional intelligence. (3) The significance value of 0.722 > 0.05 means that the use of screen time does not affect emotional intelligence. (4) The direct effect of using gadgets on emotional intelligence is explained by a beta value of 0.228. (5) The indirect effect between gadget use and screen time as an intervening variable is (-0.032 x 0.035 = (-0.00112), so 0.228 > (-0.00112), meaning that screen time is not an intervening variable between gadgets and emotional intelligence. The better a person's emotional intelligence, the better it will be accepted by the community.